The impact of building a training program on teachers and students - Mohsin Hamad, Salwa; Jasim, Basim M. (Opción, 2019)
The research aims to identify the impact of the proposed training program on mental mathematics among students of teachers who have been trained in the program. A mathematical strength test for mathematics teachers was applied. The appropriate statistical means were used to derive the results. As a result, there is a statistically significant difference at the level of (0.05) between the average scores of the mathematics students of the experimental group and the students of the control group. In conclusion, there is a clear impact of the training program on the athletic strength of teachers and mental math for students.